الرقابة الداخلية وتأثيرها في مخاطر التأمين: بحث تطبيقي في شركة التأمين الوطنية (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Individuals resort to insurance against certain risks, in order to ward off the danger in the event of their occurrence and therefore a sense of security, so they are shifting the burden of risk that they may be subjected in their persons or their property to others by contracting with an insurance company to perform this service. To achieve this it is necessary to pay the premiums and certain amounts to the insurance company, and you are investing for their development to the ability to pay them compensation for the insured in the event of a hazard insured against. Therefore, subject to the insurance business to the supervision and control of the state, albeit to varying degrees from country to country, so as to ensure the achievement of the goal of basic insurance, which is to provide insurance protection for those who wish them at a reasonable cost, and that the global consensus on the need for supervision and control of the insurance operations. The research aims to determine the role of internal control in reducing the risk of the insurance company in the sample and through the study and analysis of the concept of internal control and stages and kinds of departments and their relationship. On this basis, offered a researcher at the consideration of the subject (oversight role in reducing the risk of insurance) An Empirical Study in the National Insurance Company to choose used form questionnaire as head of the collection of information as well as personal interviews for managers, and tested hypotheses which focused on the existence and effect relationship between the variables of search by statistical methods relevant for the purpose of testing hypotheses relationship adopted Pearson correlation coefficient, and to test the effect relationship has been the adoption of simple linear regression coefficient.The research found to prove the most important results of the theoretical side of it which is the success of the internal control in any economic unit depends on how serious the desire of senior management to its success, support and because the administration is responsible for the formulation and design of the internal control system commensurate with its goals., And the most important results of the search scientifically is a relationship strong correlation between the internal control and risk insurance, and this relationship is disabled or employee in the company has a good researcher recommends more attention to and strengthen the relationship and this is in the protection of the company's exposure to risk. And in the end, the researcher presented a set of recommendations to the company researched, based on the findings was the most prominent. Paying attention to the Department of Business Administration of internal control and provide her powers, as well as the development and Staff be qualified and well-qualified plans, programs and guidelines and international standards of censorship.